Improvement of polymer adhesion by designing the interface layer. (16th January 2023) - Kawaguchi, Daisuke; Nakayama, Reika; Koga, Hiroki; Totani, Masayasu; Tanaka, Keiji
Abstract: Polymer adhesion with inorganic materials is a key technology for realizing the diversification of materials. When a polymer contacts with inorganic materials, a layer containing strongly- and loosely-adsorbed chains is formed at the surface. The former and latter are chains that adopt mainly train and loop/tail conformations, respectively. To improve the interfacial adhesion, it is of pivotal importance to control the interaction between loosely-adsorbed chains, which are in part directly attached to the solid surface, and bulk free chains. We here succeeded in increasing the interfacial strength by chemically cross-linking them. Polymer chains were attached to the surface of a silicon wafer and then a film of isotactic polypropylene or polyamide 6 was mounted on it to produce our model system. As loosely-adsorbed chains have photo-cross-linkable moieties, the polyolefin or engineering plastic film could be strongly adhered to the silicon wafer via the adsorbed layer. On the other hand, the film could be easily detached from the wafer having loosely-adsorbed chains without photo-cross-linkable groups. Our facile idea that loosely-adsorbed interfacial chains chemically bond to the polymer bulk shows promise for the design and construction of not only interfacial adhesion but also composite materials. Graphical abstract: Image 1 Highlights: A layer containing strongly- and loosely-adsorbed chains was formed at the solid surface. The layer was prepared using a combination of inert and cross-linkable chains. The layer with loosely-adsorbed cross-linkable chains was strongly adhered with an adherend. The layer with loosely-adsorbed inert chains was easily detached from the adherend. The difference of the adhesion between the above two cases is discussed.